Effects of allopurinol on exercise-induced muscle damage: new therapeutic approaches? - Sanchis-Gomar, F. (Cell Stress Chaperones, 2014)
Intensive muscular activity can trigger oxidative stress, and free radicals may hence be generated by working skeletal muscle. The role of the enzyme xanthine oxidase as a generating source of free radicals is well documented and therefore is involved in the skeletal muscle damage as well as in the potential transient cardiovascular damage induced by high-intensity physical exercise. Allopurinol is a purine hypoxanthine-based structural analog and a well-known inhibitor of xanthine oxidase. The administration of the xanthine oxidase inhibitor allopurinol may hence be regarded as promising, safe, and an economic strategy to decrease transient skeletal muscle damage (as well as heart damage, when occurring) in top-level athletes when administered before a competition or a particularly high-intensity training session. Although continuous administration of allopurinol in high-level athletes is not recommended due to its possible role in hampering training-induced adaptations, the drug might be useful in non-athletes. Exertional rhabdomyolysis is the most common form of rhabdomyolysis and affects individuals participating in a type of intense exercise to which they are not accustomed. This condition can cause exercise-related myoglobinuria, thus increasing the risk of acute renal failure and is also associated with sickle cell trait. In this manuscript, we have reviewed the recent evidence about the effects of allopurinol on exercise-induced muscle damage. More research is needed to determine whether allopurinol may be useful for preventing not only exertional rhabdomyolysis and acute renal damage but also skeletal muscle wasting in critical illness as well as in immobilized, bedridden, sarcopenic or cachectic patients.